Epidemiology and treatment of psoriasis: a Brazilian perspective - Duarte GV (Dove Medical Press, 2015)
Gleison V Duarte,1 Larissa Porto-Silva,2 Maria de Fátima Paim de Oliveira1 1Dermatology Department, Federal University of Bahia, Salvador, 2Escola Bahiana de Medicina e Saúde Pública, Salvador, BA, Brazil Abstract: Psoriasis is a chronic immune-mediated systemic disease that is influenced by genetic and environmental factors, is associated with comorbidities, and has a negative impact on the quality of life of affected individuals. The prevalence of psoriasis varies among different ethnic groups, but this topic has not been studied in Brazil to date. In this review, we evaluate the epidemiology and treatment of psoriasis from a Brazilian perspective. We focused on studies that involved Brazilian subjects. The prevalence of psoriasis in Brazil is estimated to be 2.5%, but no population study has been performed previously. Environmental factors, such as tropical climate, in association with genetic factors, such as miscegenation, may exert a beneficial impact on the course and frequency of psoriasis in Brazil. A number of studies have advanced our understanding of the cardiovascular, ophthalmic, and oral comorbidities that are associated with psoriasis. Concerns about biological therapy, such as endemic leprosy, human T-cell lymphotropic virus (HTLV), and tuberculosis infections, are discussed. The nonavailability of treatment options for psoriasis in the public health system contradicts the Brazilian Society of Dermatology guidelines, stimulating the judicialization of access to medicines in psoriasis care. Keywords: psoriasis, epidemiology, comorbidities, health services accessibility, health care disparities, insurance, health care costs